Pemilihan Metode Perbaikan Flexible Pavement Untuk Meningkatkan Efektifitas Manajemen Pemeliharaan Perkerasan Bandar Udara Juanda - Arifai, Achmad Muhyidin; Haryoseno, Muhamad Irham (Institut Transportasi dan Logistik Trisakti, 2023)
Juanda International Airport is in the second place with the most number of passenger movements from the airport managed by PT. Angkasa Pura I. This causes the quality of the pavement on movement areas at the airport's airside facilities at Juanda International Airport, to experience a decrease in quality. Periodic maintenance through routine inspections needs to be carried out. The most common type of block cracking damage found. This damage will be repaired with the most effective repair method based on the assessment factor. The methods evaluated are fog sealing, patching, and overlay. In terms of duration, cost, and work preparation, fog sealing has the lowest value. However, the durability of repair results is also very short. Patching the second position with the value of cost and duration of work is not cheap but not too expensive. This method is an effective method when considering the urgency of damage in the field. The most effective method with the highest score considering the existing pavement conditions and daily aircraft traffic is overlay. Makes a larger investment with longer work duration than other methods, but can refresh flexible pavements with up to 10 years after repair life.